TIKTOK AS SOCIAL MEDIA AND THE CONSTRUCTION OF FEMALE STUDENTS’ RELIGIOUS IDENTITY - Eka Lutfia Putri; Badriyah (Qolamuna : Jurnal Studi Islam, 2026)
This study analyzes the use of TikTok social media and its implications for the construction of religious identity among university students. Using a descriptive qualitative approach, the research was conducted at Al-Qolam University Malang over a period of two months, involving in-depth interviews and observations of female students who actively use TikTok for religious content. The findings indicate that TikTok functions as a space for the expression and negotiation of religious identity, where students act as both content creators and consumers. Although they strive to convey meaningful religious messages, many become entangled in algorithmic demands that prioritize viral content and visual aesthetics. This study affirms that TikTok is not merely a communication tool, but also an arena in which students’ religious identities are constructed and presented within a broader social context. Keywords : TikTok, Religious Identity, University Students.